Characterization of S40-like proteins and their roles in response to environmental cues and leaf senescence in rice - Zheng, Xiangzi (BMC Plant Biol, 2019)
BACKGROUND: Senescence affects the quality and yield of plants by regulating different traits of plants. A few members of S40 gene family, the barley HvS40 and the Arabidopsis AtS40–3, have been shown to play a role in leaf senescence in Barley and Arabidopsis. Although we previously reported that S40 family exist in most of plants, up to now, no more function of S40 members in plant has been demonstrated. The aim of this study was to provide the senescence related information of S40 gene family in rice as rice is a major crop that feeds about half of the human population in the world. RESULTS: A total of 16 OsS40 genes were identified from the genome database of Oryza sativa L. japonica by bioinformatics analysis. Phylogenetic analysis reveals that the 16 OsS40 proteins are classified into five groups, and 4 of the 16 members belong to group I to which also the HvS40 and AtS40–3 is assigned. S40 genes of rice show high structural similarities, as 13 out of the 16 genes have no intron and the other 3 genes have only 1 or 2 introns. The expression patterns of OsS40 genes were analyzed during natural as well as stress-induced leaf senescence in correspondence with senescence marker genes. We found that 6 of them displayed differential but clearly up-regulated transcript profiles under diverse situations of senescence, including darkness, nitrogen deficiency, hormone treatments as well as pathogen infection. Furthermore, three OsS40 proteins were identified as nuclear located proteins by transient protoplast transformation assay. CONCLUSIONS: Taking all findings together, we concluded that OsS40–1, OsS40–2, OsS40–12 and OsS40–14 genes have potential regulatory function of crosstalk among abiotic, biotic and developmental senescence in rice. Our results provide valuable baseline for functional validation studies of the rice S40 genes in rice leaf senescence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-019-1767-1) contains supplementary material, which is available to authorized users.